Neuroprotective Potential of Aromatic Herbs: Rosemary, Sage, and Lavender - Faridzadeh, Arezoo; Salimi, Yasaman; Ghasemirad, Hamidreza; Kargar, Meraj; Rashtchian, Ava; Mahmoudvand, Golnaz; Karimi, Mohammad Amin; Zerangian, Nasibeh; Jahani, Negar; Masoudi, Anahita; Sadeghian Dastjerdi, Bahare; Salavatizadeh, Marieh; et al. (Frontiers in Neuroscience, 2022)
Hundreds of millions of people around the world suffer from neurological disorders or have experienced them intermittently, which has significantly reduced their quality of life. The common treatments for neurological disorders are rather expensive and may lead to a wide variety of side effects including sleep attacks, gastrointestinal side effects, blood pressure changed, etc. Several herbal medications, on the other hand, have attracted huge popularity worldwide in the recent years due to its availability, affordable prices and few side effects. Aromatic plants, sage (Salvia officinalis), lavender (Lavandula angustifolia) and rosemary (Salvia rosmarinus) have already shown anxiolytics, anti-inflammatory, anti-oxidant and neuroprotective effects. They have also shown potential in the treatment of common neurological disorders including Alzheimer's disease, Parkinson's disease, migraine, and cognitive disorders. This review summarizes the data on the neuroprotective potential of aromatic herbs, sage, lavender and rosemary.